Impact of the Flipped and Blended Classroom on Secondary Students' English Performance, Confidence, and Perceptions in Malaysia - Mohd Syaubari; Mohd Ridhuan Bin Mohd Jamil; Roshida Binti Abu Bakar (Southeast Asian Journal of Islamic Education Management, 2024)
Producing students with high confidence in learning English who possess 21st-century skills—such as foundational literacies, competencies, and character qualities—requires a transformative shift in teaching strategies and methodologies. This study explores the effectiveness of the Flipped & Blended Classroom Program in enhancing English language performance, confidence, and perceptions among secondary school students. Utilizing a range of technological tools, diverse teaching strategies, and school resources, students were encouraged to actively engage, explore, and learn independently. A total of 400 secondary school students were randomly selected to participate in this study, completing questionnaires before and after their experience in the program. The findings reveal a significant improvement in both examination scores and classroom-based assessments, highlighting the program’s impact on academic performance. Additionally, students reported feeling more confident in their English abilities, with many expressing a more positive attitude towards learning the language. These results demonstrate that integrating technology in a structured classroom setting benefits students by fostering a more dynamic, student-centered learning environment. For teachers, the program provided opportunities to adopt innovative practices and conduct activities that challenge students, ultimately enhancing teaching quality. This study underscores the value of incorporating blended learning models in educational contexts, especially in developing essential skills for the modern world.